2019
DOI: 10.1124/dmd.118.085290
|View full text |Cite
|
Sign up to set email alerts
|

The MBNL/CELF Splicing Factors Regulate Cytosolic Sulfotransferase 4A1 Protein Expression during Cell Differentiation

Abstract: Sulfotransferase 4A1 (SULT4A1) is a sulfotransferase-like protein that is highly conserved between species. In human tissues, there are two transcripts, one that produces a full-length protein and one that produces an unstable truncated protein. The second transcript, which includes a pseudo-exon between exons 6 and 7 (6p), is widely expressed, whereas the first is more restricted. Differentiation of neuronal cells results in the removal of the pseudo-exon and subsequent SULT4A1 protein expression. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In mouse, Sult4a1 mRNA expression is low in fetal brains and remains nearly unchanged until postnatal day 30, after which a marked increase in expression has been observed (Alnouti et al, 2006). Consistent with this, SULT4A1 protein expression was found to increase during neuronal differentiation (Idris et al, 2019). Notably, Sult4a1-KO mice display severe neurological defects including tremor, rigidity and seizure and the survival of pups during postnatal development is strongly affected by loss of Sult4a1 (Garcia et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In mouse, Sult4a1 mRNA expression is low in fetal brains and remains nearly unchanged until postnatal day 30, after which a marked increase in expression has been observed (Alnouti et al, 2006). Consistent with this, SULT4A1 protein expression was found to increase during neuronal differentiation (Idris et al, 2019). Notably, Sult4a1-KO mice display severe neurological defects including tremor, rigidity and seizure and the survival of pups during postnatal development is strongly affected by loss of Sult4a1 (Garcia et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
“…However, the functional role of SULT4A1 within neuronal development is largely unknown since no substrate nor biological functions have been identified yet. SULT4A1 mRNA and protein expression were found to increase during mouse neuron and brain development (Alnouti et al, 2006;Hashiguchi et al, 2018;Idris et al, 2019), supporting a role for SULT4A1 in neuronal maturation. Notably, we found that SULT4A1 is not only express in cytosol, mitochondrial and microsomal fractions (Garcia et al, 2018), but is also highly expressed in synaptosomal preparation, obtained from mouse cortical neurons (Fig.…”
Section: Discussionmentioning
confidence: 78%